Estimating stand parameters of a 114- year-old Japanese larch plantation using UAV photogrammetry - Jeyavanan, K.; Owari, T.; Hiroshima, T.; Tsuyuki, S. (Japanese Forest Society, 2023)
An old-growth plantation is an iconic site that has great value. Assessing stand parameters is laborious and time-consuming in the field. Therefore, this case study aimed to estimate the stand parameters of a 114-year-old Japanese larch (Larix kaempheri) using UAV photogrammetry in Northern Japan. First, 3D point clouds and orthomosaic were generated through SfM technology from the imagery at two UAV altitudes, 80 m, and 120 m. Then, a canopy height model (CHM) was generated by subtracting LiDAR DTM from UAV DSM. We used a Shiny-based R package for individual tree detection (ITD), tree height (TH) and crown area (CA) from the CHM. We also used local maxima algorithm for ITD. Stand density, mean TH, and CA cover were estimated from ITD, TH and CA. Results of accuracy were tested using F-Score, R 2 and RMSE against field data and manually delineated CA. The maximum height of CHM was 43.66 m and 44.21 m at the UAV flight 80 m and 120 m, respectively whereas the field maximum TH was 42.9 m.